Statistical process control in spraying using unmanned aerial vehicle in conilon coffee crop - Moro Soela, Débora; Leandro da Vitória, Edney; Furtado de Oliveira, Ronaldo; Hoffmam Crause, Deborah; s Freitas, Ismael Lourenço de Jesu; Locatelli, Tamara (Brazilian Journal of Production Engineering, 2020)
Statistical Process Control is an important tool for detecting and adjusting the improvement of variability and increasing the quality of agricultural sprays. The objective of this work was to evaluate the quality and variability, through statistical process control, of the deposition of sprayed syrup on the leaves of the coffee tree and the loss to the soil, promoted by the application with Unmanned Aerial Vehicle at different heights of spraying on two Conilon coffee genotypes.The experiment was carried out in a Conilon coffee plantation in 2018, with a completely randomized design in a factorial scheme 3 x 2 factorial scheme, with three flight operating heights in relation to the coffee canopy (1.0, 1.5 and 2.0 m) and two genotypes of conilon coffee (A1 and Bamburral), with 12 repetitions per treatment. Was used spectrophotometry to quantify, by, the syrup deposits on the leaves of the upper and lower part and the runoff on the soil. The statistical quality of the sprayings was evaluated, using statistical process control. Through the control charts, no non-random patterns were detected within the treatments, ensuring the good quality of the applications carried out in the coffee culture. All treatments were within the limits, but at the 1.0 m flight height and the A1 genotype, they showed the best results of upper and lower deposition.
Keywords: Deposition; runoff; application technology